Reliability of supply chains in a random environment - Andronov, A. M.; Jurkina, T. (Automatic control and computer sciences, 2015)
A supply chain is considered that operates in a random environment.The last is described by continuous-time finite irreducible Markov chain. Each state of the environment (the Markov chain) has its own probability of fatal failure as a result of the breakdown of the supply. There are algorithms for calculating the reliability of the chain (a probability of a successful supply) and the distribution function of the successful performance time presented in this paper. The numerical example illustrates the suggested approach.